Nutrient-induced antibiotic resistance in Enterococcus faecalis in the eutrophic environment. (December 2016) - Ali, Liaqat; Wang, Yan-Qiu; Zhang, Jie; Ajmal, Muhammad; Xiao, Zhengrun; Wu, Jiarong; Chen, Ji-Long; Yu, Daojin
Highlights: Antibiotic resistance of waterborne enterococci varied in mesocosm environments. Adding different concentrations of N and P caused enterococci resistance to OXY, CHL and ERY. OXY resistance level was 100% by Day 60 in the nutrient-enriched mesocosms. Incidences of tet (L) and tet (S) were 62.2% and 18.9%, respectively, in 37 OXY-resistant E. faecalis strains. Enterococcus faecalis developed resistance to ERY rapidly. Abstract: Nutrient deposition and extensive use of antibiotics are increasing worldwide, especially in freshwater ecosystems. Bacteria display resistance to certain antibiotics and thus survive for extended periods in eutrophic environments. In this study, model ecosystems were established to investigate the effect of nitrate and phosphate nutrient salts on antibiotic resistance in strains of Enterococcus faecalis . Mesocosms were replicated to evaluate the ecological effects of nutrient influx. The mesocosms were divided into four different nitrogen (N) and phosphorus (P) regimens. Enterococcus faecalis strains were isolated on Days 0, 1, 7, 14, 21, 28, 40, 60 and 95 to evaluate their sensitivity to ampicillin, oxytetracycline (OXY), ciprofloxacin (CIP), chloramphenicol (CHL), vancomycin and erythromycin (ERY). Resistance genes for ERY ( ermB, msrC and mefA ), OXY [ tet (M), tet (L) and tet (S)] and CHL ( cat ) as well as the enterococcal surface protein gene ( esp ) were investigated by PCR. The total nitrogen, total phosphorus, chemical oxygen demand permanganate index (CODMn ), chlorophyll-a, Secchi depth and trophic level index were observed. In conclusion, addition of N and P had a significant influence on the resistance phenotypes of E. faecalis to OXY, CHL and ERY. Only high dosage led to CIP resistance. Higher total N concentrations resulted in the development of relatively higher resistance to OXY and CIP. The resistance genes tet (L) and tet (S) for OXY, msrC for ERY and cat for CHL were found to be associated with resistance in E . faecalis .